Systems theory and social work/social pedagogy - Wagner, Harald (Socialinė teorija, empirija, politika ir praktika, 2003)
There is a need for the reflection in social work as in other professions. The area, problems and methods of social work are complex and it requires high quality competences. The goal of social work science is to solve these problems, but it is not yet established. Meanwhile social workers have to interact with the complexity in social work and it would be good to have a common theoretical framework at the hand. The theory of systems theory can take that role. The goal of the article is to present and review a systems theory and to describe the potentials of the theory to solve the complexity in social work. The main concepts of the theory are presented and illustrated by the examples of social work practice.